Quality improvement initiative using transcutaneous bilirubin nomogram to decrease serum bilirubin sampling in low-risk babies - Muhammad Hussain Shah; Shabina Ariff; Syed Rehan Ali; Rayaan Asad Chaudhry; Maryam Pyar Ali Lakhdir; Fatima Qaiser; Simon Demas; Ali Shabbir Hussain (BMJ Paediatrics Open)
Background Screening for neonatal hyperbilirubinaemia in the postnatal ward has traditionally been performed using serum bilirubin sampling, but this has significant drawbacks such as risk of infection and slower reporting time.Objective We aimed to assess the impact of introducing transcutaneous bilirubin (TcBR) testing using TcBR nomogram on the number of serum bilirubin samples sent.Methods A before-and-after study was performed following the introduction of a protocol integrating the use of the Dragger JM-105 transcutaneous bilirubinometer in the postnatal ward. Only babies born at ≥37 weeks of gestation, weighing ≥2500 g who presented with jaundice after the first 24 hours and within the first 7 days of life were included in the study. The number of total serum bilirubin samples (TSBRs) sent were compared for the 6-month periods before and after (a total of 12 months) implementation of the new protocol.Results In the pre-implementation phase, a total of 882 (49%) out of 1815 babies had at least one serum bilirubin sample taken as opposed to a total of 236 (17%) out of 1394 babies in the post-implementation phase. The odds of performing TSBRs at least one time among babies in post-implementation phase were 79% lower than in pre-implementation phase (OR 0.21, 95% CI 0.18 to 0.25). We also estimated a significant cost saving of approximately US$1800 over a period of 6 monthsConclusion TcBR testing used in conjunction with our proposed nomogram significantly reduces the need for serum bilirubin sampling.